POTENSI PERMAINAN TRADISIONAL BAKIAK DALAM MENGEMBANGKAN SIKAP KERJASAMA PADA SISWA KELAS IV SD SWASTA MUHAMMADIYAH 37 TANJUNG SELAMAT - Cut Ayu Andira; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
The aim of this research is to describe the potential of traditional games in developing cooperative attitudes in fourth grade students at the Muhammadiyah Tanjung Selamat Private Elementary School, which is based on a lack of cooperative attitudes among students, a lack of concern for their surroundings. To obtain data in this research, the author used qualitative research methods from data produced through observation, interviews and documentation. The theory in this research uses the Ethno Pedagogical theory, namely educational praxis based on local wisdom and viewing local wisdom as a source of innovation and skills that can be empowered. This research was conducted on fourth grade students at the Tanjung Selamat Muhammadiyah Private Elementary School, with a total of 28 students. This research produced findings, namely: 1) The role of the traditional clog game in developing students' cooperative attitudes. 2) the development of students' attitudes after playing the traditional game of bakiak, namely: when studying, groups of students respect each other and are willing to listen to suggestions from group members, there is a reduction in disputes between students, and there is visible solidarity among students with each other. Keywords: Traditional games, Collaborative Attitude